Investigation of the effect of technological parameters on efficiency of chemical string cutting of semiconductor materials - Kravetsky, M.Yu.; Sypko, S.A.; Fomin, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
On the basis of the balance model for convection-diffusion processes that occur during string chemical cutting (CC) of samples, we derive an analytical expression for the limiting CC rate at maximal use of etching agent. Comparison between the experimental and theoretical dependencies of CC rates for InSb, HgCdTe and CdTe samples on the velocity of string motion and diameter of sample being cut demonstrates good agreement of the experimental results with the model notions. It is shown that diffusion kinetics of the CC process is retained even at very high velocities of string motion. The experimentally obtained value of CC rate is approaching 3 mm/min. The dependencies studied point at resources for increase of CC efficiency. Some technical modification of the equipment, related primarily to increasing velocity of motion of the etching liquid carrier, will make the CC technique able to meet competition with the abrasion techniques in technological lines for manufacturing of semiconductor devices.